Asuhan Keperawatan Pemenuhan Rasa Nyaman Nyeri Pada Pasien Hipertensi Dengan Tindakan Kompres Hangat Pada Leher Di Rumah Sakit Tk II Putri Hijau Medan Tahun 2022 - Chairreza Rachman; Purwaningsih Purwaningsih; Erita Gustina (LPPM STIKES Siti Hajar dan Insight Power, 2022)
Background: Background: Hypertension is a disease with a symptom of systolic and diastolic blood pressure disorder; it increases above normal blood pressure. According to the World Health Organization (WHO) in 2019, hypertension is a number one killer. It kills about eight million people each year throughout the world. Its prevalence in North Sumatera reaches 6.7% of the population in North Sumatera, based on the data from the Litbangkes of the Ministry of Health. It means that 12.42 million people in some districts of North Sumatera suffer from hypertension. Method: The research uses descriptive method with case study approach which includes the stages of analyzing, Nursing Diagnoses, nursing intervention, nursing implementation, and nursing evaluation in two hypertension patients in the Putri Hijau Level II Hospital. Result: It is found that in the post-nursing intervention by giving warm compress, both patients feel comfortable and their pain decrease. Conclusion: Warm compress on the throat of hypertension patients can decrease pain. Suggestion: It is recommended that hypertension patients apply warm compress on their throats.Keyword: hypertension, warm compress, in an adult patient